Answer:
<u>1 step:</u> Raise both sides of the equation to the power of 2.
<u>2 step:</u> Simplify to obtain the final radical term on one side of the equation.
<u>3 step:</u> Raise both sides of the equation to the power of 2 again.
<u>4 step: </u>Simplify to get a quadratic equation.
<u>5 step:</u> Use the quadratic formula to find the values of x.
<u>6 step:</u> Apply the Zero Product Rule.
Step-by-step explanation:
Given the equation
![\sqrt{x+3}-\sqrt{2x-1}=-2](https://tex.z-dn.net/?f=%5Csqrt%7Bx%2B3%7D-%5Csqrt%7B2x-1%7D%3D-2)
<u>1 step:</u> Raise both sides of the equation to the power of 2.
![(\sqrt{x+3}-\sqrt{2x-1})^2=(-2)^2\\ \\(\sqrt{x+3})^2-2\sqrt{x+3}\sqrt{2x-1}+(\sqrt{2x-1})^2=4\\ \\x+3-2\sqrt{x+3}\sqrt{2x-1}+2x-1=4](https://tex.z-dn.net/?f=%28%5Csqrt%7Bx%2B3%7D-%5Csqrt%7B2x-1%7D%29%5E2%3D%28-2%29%5E2%5C%5C%20%5C%5C%28%5Csqrt%7Bx%2B3%7D%29%5E2-2%5Csqrt%7Bx%2B3%7D%5Csqrt%7B2x-1%7D%2B%28%5Csqrt%7B2x-1%7D%29%5E2%3D4%5C%5C%20%5C%5Cx%2B3-2%5Csqrt%7Bx%2B3%7D%5Csqrt%7B2x-1%7D%2B2x-1%3D4)
<u>2 step:</u> Simplify to obtain the final radical term on one side of the equation.
![x+3-2\sqrt{x+3}\sqrt{2x-1}+2x-1=4\\ \\3x+2-2\sqrt{x+3}\sqrt{2x-1}=4\\ \\-2\sqrt{x+3}\sqrt{2x-1}=4-3x-2\\ \\-2\sqrt{x+3}\sqrt{2x-1}=2-3x](https://tex.z-dn.net/?f=x%2B3-2%5Csqrt%7Bx%2B3%7D%5Csqrt%7B2x-1%7D%2B2x-1%3D4%5C%5C%20%5C%5C3x%2B2-2%5Csqrt%7Bx%2B3%7D%5Csqrt%7B2x-1%7D%3D4%5C%5C%20%5C%5C-2%5Csqrt%7Bx%2B3%7D%5Csqrt%7B2x-1%7D%3D4-3x-2%5C%5C%20%5C%5C-2%5Csqrt%7Bx%2B3%7D%5Csqrt%7B2x-1%7D%3D2-3x)
<u>3 step:</u> Raise both sides of the equation to the power of 2 again.
![(-2\sqrt{x+3}\sqrt{2x-1})^2=(2-3x)^2\\ \\4(x+3)(2x-1)=(2-3x)^2](https://tex.z-dn.net/?f=%28-2%5Csqrt%7Bx%2B3%7D%5Csqrt%7B2x-1%7D%29%5E2%3D%282-3x%29%5E2%5C%5C%20%5C%5C4%28x%2B3%29%282x-1%29%3D%282-3x%29%5E2)
<u>4 step: </u>Simplify to get a quadratic equation.
![4(2x^2-x+6x-3)=2^2-2\cdot 2\cdot 3x+(3x)^2\\ \\8x^2-4x+24x-12=4-12x+9x^2\\ \\8x^2+20x-12-4+12x-9x^2=0\\ \\-x^2+32x-16=0\\ \\x^2-32x+16=0](https://tex.z-dn.net/?f=4%282x%5E2-x%2B6x-3%29%3D2%5E2-2%5Ccdot%202%5Ccdot%203x%2B%283x%29%5E2%5C%5C%20%5C%5C8x%5E2-4x%2B24x-12%3D4-12x%2B9x%5E2%5C%5C%20%5C%5C8x%5E2%2B20x-12-4%2B12x-9x%5E2%3D0%5C%5C%20%5C%5C-x%5E2%2B32x-16%3D0%5C%5C%20%5C%5Cx%5E2-32x%2B16%3D0)
<u>5 step:</u> Use the quadratic formula to find the values of x.
![D=(-32)^2-4\cdot 1\cdot 16=1,024-64=960\\ \\x_{1,2}=\dfrac{-(-32)\pm \sqrt{960}}{2\cdot 1}=\dfrac{32\pm 8\sqrt{15}}{2}=16\pm 4\sqrt{15}](https://tex.z-dn.net/?f=D%3D%28-32%29%5E2-4%5Ccdot%201%5Ccdot%2016%3D1%2C024-64%3D960%5C%5C%20%5C%5Cx_%7B1%2C2%7D%3D%5Cdfrac%7B-%28-32%29%5Cpm%20%5Csqrt%7B960%7D%7D%7B2%5Ccdot%201%7D%3D%5Cdfrac%7B32%5Cpm%208%5Csqrt%7B15%7D%7D%7B2%7D%3D16%5Cpm%204%5Csqrt%7B15%7D)
Then the equation is
![(x-16-4\sqrt{15})(x-16+4\sqrt{15})=0](https://tex.z-dn.net/?f=%28x-16-4%5Csqrt%7B15%7D%29%28x-16%2B4%5Csqrt%7B15%7D%29%3D0)
<u>6 step:</u> Apply the Zero Product Rule.
![(x-16-4\sqrt{15})(x-16+4\sqrt{15})=0\\ \\x-16-4\sqrt{15}=0\text{ or }x-16+4\sqrt{15}=0\\ \\x_1=16+4\sqrt{15}\text{ or }x_2=16-4\sqrt{15}](https://tex.z-dn.net/?f=%28x-16-4%5Csqrt%7B15%7D%29%28x-16%2B4%5Csqrt%7B15%7D%29%3D0%5C%5C%20%5C%5Cx-16-4%5Csqrt%7B15%7D%3D0%5Ctext%7B%20or%20%7Dx-16%2B4%5Csqrt%7B15%7D%3D0%5C%5C%20%5C%5Cx_1%3D16%2B4%5Csqrt%7B15%7D%5Ctext%7B%20or%20%7Dx_2%3D16-4%5Csqrt%7B15%7D)